The photophysics of perovskite emitters: from ensemble to single particle - Feng, Minjun (2024)
Halide perovskite emitters are a groundbreaking class of optoelectronic materials possessing remarkable photophysical properties for diverse applications. In perovskite light emitting devices, they have achieved external quantum efficiencies exceeding 28%, showcasing their potential for next-generation solid-state lighting and ultra high definition displays. Furthermore, the demonstration of room temperature continuous-wave perovskite lasing underscores their potential for integrated optoelectronics. Of late, perovskite emitters are also found to exhibit desirable single-photon emission characteristics as well as superfluorescence or superradiance phenomena for quantum optics. With progressive advances in synthesis, surface engineering, and encapsulation, halide perovskite emitters are poised to become key components in quantum optical technologies. Understanding the underpinning photophysical mechanisms is crucial for engineering these novel emergent quantum materials. This review aims to provide a condensed overview of the current state of halide perovskite emitter research covering both established and fledging applications, distill the underlying mechanisms, and offer insights into future directions for this rapidly evolving field.